1997
DOI: 10.1176/ajp.154.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain hemodynamic responses during passive orthostatic challenge in panic disorder

Abstract: Patients with panic disorder, both during the acute phase of the illness and after clinical recovery, show an exaggerated drop in CBF during tilting. Since these findings are similar, although attenuated in intensity, to those which are observed in dysautonomic illnesses, one possible interpretation is that of panic disorder as a subclinical form of autonomic dysreactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…In accordance with our findings, an exaggerated drop in cerebral blood flow has been reported in patients with panic disorder, similar to that observed in patients with VVS [25,36,37,38]. A predominant vagal activity has also been observed in patients with blood phobia [39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our findings, an exaggerated drop in cerebral blood flow has been reported in patients with panic disorder, similar to that observed in patients with VVS [25,36,37,38]. A predominant vagal activity has also been observed in patients with blood phobia [39].…”
Section: Discussionsupporting
confidence: 92%
“…Panic disorder has been associated with autonomic dysreactivity [25,26,27,28,29,30]. It has also been reported that panic symptoms reappear in 42% of patients after hyperventilation, a maneuver that has been associated with the vasovagal reflex [31,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…There is paucity of studies on biological markers of remitted patients with panic disorder [94, 95, 96, 97]. Six patients with panic disorder who had panicked during sodium lactate infusion were given cognitive-behavioral treatment.…”
Section: Subclinical Symptoms Of Panic Disordermentioning
confidence: 99%
“…Cardio-cerebrovascular modulation, which is related to responses of the autonomic nervous system, has the function of regulating cerebral blood flow [35]. Several studies, such as Alkin et al and Faravelli et al, have focused on cardio-cerebrovascular modulation in panic disorder and have found some significant results [68]; however the characteristics of cardio-cerebrovascular modulation in patients with GAD are largely unknown.…”
Section: Introductionmentioning
confidence: 99%